1987
DOI: 10.1111/j.1365-2125.1987.tb03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous and oral sodium 2‐mercaptoethane sulphonate (mesna) in normal subjects.

Abstract: The pharmacokinetics of mesna (sodium 2‐mercaptoethane sulphonate) and its inactive disulphide, dimesna, were investigated using high performance liquid chromatography in six normal subjects following intravenous and oral administration of 800 mg mesna. The mean maximum mesna concentration after i.v. administration was 111 (s.d. +/‐ 28.3) nmol ml‐1 and the mean maximum dimesna concentration was 183 (s.d. +/‐ 41.6) nmol ml‐1. Following oral mesna dosing the mean peak mesna concentration was 19.6 (s.d. +/‐ 10.2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…It was shown that concomitant 2-mercaptosulfonic acid (mesna) administration protects the urothel from IFOtherapy-induced damage, such as hemorrhagic cystitis. Mesna is oxidized by ethylenediaminetetraacetic acid (EDTA) inhibitable constituents in the blood to the physiologically inert disulphide metabolite dimesna, which is excreted by the kidneys [11][12][13]. Part of the filtered dimesna is taken up into renal tubule cells and reduced to mesna [14].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that concomitant 2-mercaptosulfonic acid (mesna) administration protects the urothel from IFOtherapy-induced damage, such as hemorrhagic cystitis. Mesna is oxidized by ethylenediaminetetraacetic acid (EDTA) inhibitable constituents in the blood to the physiologically inert disulphide metabolite dimesna, which is excreted by the kidneys [11][12][13]. Part of the filtered dimesna is taken up into renal tubule cells and reduced to mesna [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since much lower plasma concentrations of free mesna are seen after oral administration (James et al, 1987) the effect of oral mesna on the thiol status was also investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Since much lower plasma concentrations of free mesna are seen after oral administration (James et al, 1987) (Aebi et al, 1991). Total mesna and cyst(e)ine in urine were measured following the same protocol as for disulfides in plasma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were deproteinised and the total amount of mesna and BNP7787 was measured by HPLC (with electrochemical detection) according to the method described (James et al, 1987;El-Yazigi et al, 1997;Verschraagen et al, 2001). For the analysis of total platinum, intact cisplatin, monohydrated cisplatin and unbound platinum, plasma samples were collected just before treatment and at 0.5, 1, 1.5, 2, 3, 4 and 6 h after the start of the cisplatin infusion.…”
Section: Pharmacokineticsmentioning
confidence: 99%